Learning Path Scrum Practitioner - Norman, Tommy (Addison-Wesley Professional, 2016)
Overview This Learning Path includes Scrum Fundamentals LiveLessons , Advanced Scrum LiveLessons , and Lean Principles for Scrum LiveLessons . Prerequisites Familiarity with the basics of software development projects. Description Scrum Fundamentals LiveLessons provides helpful insight into the history of Agile and how its values and principles can focus teams on consistently delivering quality products that immediately add customer value. It covers the complete Scrum framework from project initiation and executing Sprints to delivering a product increment. Many teams adopting Scrum struggle with how to manage requirements and integrate their quality assurance efforts into their Agile processes. Advanced Scrum LiveLessons provides a deep dive into both of these areas, exploring how to apply the values and principles of Agile and Scrum to avoid common pitfalls. For companies that have implemented Scrum, applying Lean will amplify their Scrum implementations and development cycles. Lean Principles of Scrum LiveLessons will demonstrate how to apply Lean methods to Scrum. Part I of this LiveLessons course covers Lean and Kanban principles and patterns to provide learners a solid understanding for where Lean came from and an overview of its various principles. Part II of this course concentrates on taking what was learned in Part 1 and integrating those principles into a Scrum implementation. About the Instructor Tommy Norman is the Agile Practice Lead at the Holland Square Group in Nashville, TN. For over 17 years he has been helping clients build solutions using both Agile and traditional approaches as a CSM/CSP Scrum Alliance (https://www.scrumalliance.org), PSM I Scrum.org, and a 6 year recipient of Microsoft's MVP award in Application Lifecycle Management http://mvp.microsoft.com/en-us/MVP/Tommy%20Norman-4025029. Tommy is the coordinator for the Agile Nashville User Group http://agilenashville.com/ and a contributor to InformIt.com http://www.informit.com/authors/bio/d6c00a09-c490-4784-849c-e9d3e30a4cd5" and Safari Books Online, as well as a frequent speaker at regional and national events. He blogs about Agile and ALM at www.tommynorman.com and rambles about most everything on Twitter as https://twitter.com/tommynorman tommynorman. About LiveLessons Video Training The LiveLessons Video Training series publishes hundreds of hands-on, expert-led video tutorials covering a wide selection of technology topics designed to teach you the skill...
Online resource; Title from title screen (viewed August 23, 2016)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos